The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.15405/epsbs.2018.12.173
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Features Of Competitiveness Of University Students

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Noncommercial 4.0 Unported License, permitting all non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The system of scientific circles should be considered as an obligatory part of the curriculum and implemented during the first and second training years. Foreign students are interested in group classes, as they understand that their competitiveness [17] in the labor market both depends on their knowledge of linguistic and speech literacy standards, cultural training, creativity of approaches, etc. This belief is formed in the process of everyday educational practice.…”
Section: Resultsmentioning
confidence: 99%
“…The system of scientific circles should be considered as an obligatory part of the curriculum and implemented during the first and second training years. Foreign students are interested in group classes, as they understand that their competitiveness [17] in the labor market both depends on their knowledge of linguistic and speech literacy standards, cultural training, creativity of approaches, etc. This belief is formed in the process of everyday educational practice.…”
Section: Resultsmentioning
confidence: 99%
“…Requirements to the intellectual and creative abilities of a person, to his psychological characteristics are increasing [12]. There will be a problem with the unemployed people who are in active age, but whose abilities to work will not meet the new requirements.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have found that a high level of emotional intelligence development contributes to success in various spheres of human life, such as law, education, medicine. Moreover, the development of employees' abilities in the communicative and emotional sphere has a positive impact on their professional activities (Macnamara J., 2018;Solovieva O. V., Bondarenko O.S., 2018;Nasilenko L.A., 2013;Tretyakov V.S., Ignatenko A.A., 2012;Petrovskaya A.S., 2007., Zakharova, A.N. et al, 2018Zakharova, A.N.…”
Section: Introductionmentioning
confidence: 99%